'Tomorrow belongs to us'
1 online resource
Keywords: "This book traces the varied development of the far right in Britain from the formation of the National Front in 1967 to the present day. Experts draw on a range of disciplinary and methodological perspectives to provide a rich and detailed account of the evolution of the various strands of the contemporary far right over the course of the last fifty years. The book examines a broad range of subjects, including Holocaust denial, neo-Nazi groupuscularity, transnational activities, ideology, cultural engagement, homosexuality, gender and activist mobilisation. It also includes a detailed literature review. This book is essential reading for students of fascism, racism and contemporary British cultural and political history."--Provided by publisher.